Mortality of laying hens associated with the failure of electricity supply in an acclimated shed and in a non-acclimated one - Pereira, Danilo Florentino [UNESP]; Kodaira, Vanessa [UNESP]; De Freitas Bueno, Leda Gobbo [UNESP]; Soares, Nilce Maria; Salgado, Douglas D'Alessandro; Lelis, Ana Laura Januário [UNESP] (My University, 2015)
Thermal envimnment directly influences the performance of birds and the temperature rise caused by the heat fmm birds and external environment may result in losses such as increased mortality. To minimize these losses, companies producing eggs have installed acclimatization systems on their farms, using exhausting fans and pads cooling that require more electricity than conventional sheds. However, companies do not record the energy consumption of their equipment and are unaware of the quality of supply and the cost of electricity. This study aimed to compare the consumption in two aviaries, one with acclimatization system and other non-acclimated one, to check the quality of electricity supply and correlate it with mortality of birds. The research was conducted between the months of April 2013 and April 2014. Thermal environment of both aviaries was compared through dry bulb temperature values (DBT), relative humidity (RH) and black globe temperature (BGT) recorded by data loggers distributed inside the sheds. Black Globe Temperature and Humidity Index (BGHI) was calculated from the collected data. All data were compared by Mann-Whitney test at 5% of significance. Number of dead birds was recorded daily for viability determination. Electricity consumption was recorded daily, every 30 minutes, through registers installed in the circuits of the aviaries, allowing the calculation of energy consumption and evaluation of the quality of the supply of this energy. The supply of electricity was classified as adequate, precarious and critical. The acclimated shed provided a better thermal environment than the non-acclimated one. The acclimated shed demanded around 37.6 times more energy than the other one. Interruptions in electricity supply were recorded in times of higher temperature, which resulted in significant increase in mortality of birds in the acclimated shed, reaching 1.0 and 1.2% of the flock in two incidents recorded.
Keywords: Animal welfare; Heat stress; Monitoring; Poultry housing